Efektivitas Giemsa sebagai Pengganti Pewarna Papanicolaou pada Sitologi Urin - Salim, Jesslyn Widya; Aditya, Christian Dame; Purba, Christine Vania; Sau, Kasamira Sukacita Uliarti; Lusiana, Diana Intan Gabriella; Setyoningrum, Fransisca Probo (Lembaga Teewan Journal Solutions, 2026)
Papanicolaou staining is a common or most frequently used staining method in cytology because it provides a highly detailed view of cell nuclei and cytoplasmic transparency. Giemsa staining is generally used on blood smears, but it can also provide a highly detailed view of cells, including epithelial cells. This study aims to investigate and evaluate the effectiveness of Giemsa staining as a substitute for Papanicolaou staining in urinary cytology. The research method employed was a descriptive experimental laboratory study evaluating twenty urine cytology slides stained with a 25% Giemsa solution, using Papanicolaou staining as the reference method. The slides were evaluated based on cell morphology, nuclear contrast, cytoplasmic contrast, and background clarity. Most of the urine cytology slides stained with Giemsa were classified as “Good” (50%) or “Very Good” (35%), with no slides classified as “Not Good.” Giemsa staining preserves nuclear morphology but shows lower cytoplasmic transparency compared to Papanicolaou staining.